DEVELOPMENT OF ELEMENTARY MATHEMATICS USING CONCRETE TEACHING AIDS ON FRACTION ADDITION OPERATIONS FOR GRADE V STUDENTS - Dul Azis; Takyun; Fahrudin (Schola, 2025)
Mathematics learning on fraction addition in elementary schools still demonstrates low levels of students’ conceptual understanding. This condition is largely caused by the abstract nature of fraction concepts and the limited use of concrete learning media in classroom instruction. This study aims to develop and implement a concrete teaching aid known as the Rainbow Board to support the teaching of fraction addition for fifth-grade elementary school students. The research employed an instructional development method consisting of five stages: analysis, design, development, implementation, and evaluation. The implementation was conducted with fifth-grade students of SDN Cintamanik 02 through group-based learning activities that utilized colored fraction pieces as visual representations of fraction addition concepts. The results of the study indicate that the use of the Rainbow Board had a positive impact on students’ conceptual understanding and learning outcomes. The average student score increased from 63.85 before the use of the teaching aid to 81.15 after its implementation. These findings demonstrate that the Rainbow Board is effective in transforming abstract fraction addition concepts into concrete and meaningful learning experiences, thereby enhancing students’ understanding in elementary mathematics learning. Keywords: concrete teaching aids; rainbow board; fraction addition; elementary mathematics